Rare presence and function of neuroendocrine cells in the nasal mucosa - Wils, Tine; Backaert, Wout; Jacobs, Inge; Ruysseveldt, Emma; Cremer, Jonathan; Dilissen, Ellen; Bullens, Dominique M.; Talavera, Karel; Steelant, Brecht; Van Gerven, Laura; Martens, Katleen; Hellings, Peter W. (Frontiers in Immunology, 2024)
There is growing evidence that neurogenic inflammation contributes to the pathophysiology of upper airway diseases, with nasal hyperreactivity (NHR) being a key symptom. The rare neuroendocrine cells (NECs) in the epithelium have been linked to the pathophysiology of bronchial and intestinal hyperreactivity, however their presence in the nasal mucosa and their potential role in NHR remains unclear. Therefore, we studied the presence of NECs in the nasal epithelium of controls, allergic rhinitis patients and chronic rhinosinusitis with nasal polyps patients, and their link to NHR. The expression of typical NECs markers, CHGA, ASCL1 and CGRP, were evaluated on gene and protein level in human samples using real-time quantitative PCR (RT-qPCR), western blot, immunohistochemistry fluorescence staining, RNA scope assay, flow cytometry and single cell RNA-sequencing. Furthermore, the change in peak nasal inspiratory flow after cold dry air provocation and visual analogue scale scores were used to evaluate NHR or disease severity, respectively. Limited gene expression of the NECs markers CHGA and ASCL1 was measured in patients with upper airway diseases and controls. Gene expression of these markers did not correlate with NHR severity nor disease severity. In vitro, CHGA and ASCL1 expression was also evaluated in primary nasal epithelial cell cultures from patients with upper airway disease and controls using RT-qPCR and western blot. Both on gene and protein level only limited CHGA and ASCL1 expression was found. Additionally, NECs were studied in nasal biopsies of patients with upper airway diseases and controls using immunohistochemistry fluorescence staining, RNA scope and flow cytometry. Unlike in ileum samples, CHGA could not be detected in nasal biopsies of patients with upper airway diseases and control subjects. Lastly, single cell RNA-sequencing of upper airway tissue could not identify a NEC cluster. In summary, in contrast to the bronchi and gut, there is only limited evidence for the presence of NECs in the nasal mucosa, and without correlation with NHR, thereby questioning the relevance of NECs in upper airway pathology.